2019
DOI: 10.15766/mep_2374-8265.10844
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Assessment in a Primary Care Environment: A Standardized Patient Case Activity for Interprofessional Students

Abstract: Introduction: Given the aging population and the benefits of comprehensive geriatric assessment to this subset of patients, an interprofessional education training approach may be advantageous for learners from a number of different health professions. Methods: Through intercollegiate collaborations involving seven different colleges, an interprofessional simulation using standardized patients was developed and instituted for learners in medicine, nursing, pharmacy, occupational therapy, physical therapy, dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…The participants of this large‐group simulation appreciated the interprofessional execution of the event, as well as the innovative way of making the simulation available for both students and professionals. Moreover, the participants were inspired by the possibility to learn from one another (Joyal, Katz, Harder, & Dean, 2015; Karpa et al., 2020) and the interaction between the different professions (Wietholter et al., 2017). Practicing interprofessional work enables students to apply learning contents and collaborate with different professions similarly as in working life (Johnston et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The participants of this large‐group simulation appreciated the interprofessional execution of the event, as well as the innovative way of making the simulation available for both students and professionals. Moreover, the participants were inspired by the possibility to learn from one another (Joyal, Katz, Harder, & Dean, 2015; Karpa et al., 2020) and the interaction between the different professions (Wietholter et al., 2017). Practicing interprofessional work enables students to apply learning contents and collaborate with different professions similarly as in working life (Johnston et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…3,12,14,16,19,[23][24][25][26][27][28][29] Example case study topics used to help engage students from both disciplines include hospital-acquired infections, 23 oral cancer, 28 professional roles and values 14 and ethics. 25,30,31 The study by Wilhelm et al involved pharmacy and dentistry student teams analysing ethical decision-making processes via case studies and showed significant improvements in pre/post ethics knowledge quiz scores and student perception surveys were highly favourable towards the IPE case-based activity. 25 Other case-based team IPE activities have focused on improving collaborative attitudes during the early training of health professional students to generate positive attitudes and influence students' ability to become effective health care team members.…”
Section: Case Studiesmentioning
confidence: 99%
“…Simulation activities have been shown to be an effective educational strategy for patient-centered health care education through active learning and reflective observations. 6 The low-stakes environment of simulation can create an active learning scenario with ample time for feedback and reflection for the student. 6 In the same vein, interprofessional education (IPE) facilitates learner education by improving interprofessional collaboration and respect for other health care disciplines.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The low-stakes environment of simulation can create an active learning scenario with ample time for feedback and reflection for the student. 6 In the same vein, interprofessional education (IPE) facilitates learner education by improving interprofessional collaboration and respect for other health care disciplines. 7 It has been theorized that incorporation of IPE into the early stages of learner training may translate to improving interprofessional collaboration while in professional practice.…”
Section: Introductionmentioning
confidence: 99%